ANALISIS PELUANG MERGER BANK PERKREDITAN RAKYAT TERHADAP KINERJA BANK (STUDI KASUS BANK PERKREDITAN RAKYAT BAHTERAMAS DI PROVINSI SULAWESI TENGGARA) - Maria Regina Rosario Sianturi; Cepi Pahlevi; Muhammad Sobarsyah (Master of Management, Faculty of Economics and Business, Hasanuddin University., 2018)
Good company performance can be seen from its efficiency. This study aims to determine to know the effect of merger by Rural Banks of Bahteramas in Southeast Sulawesi Province to the financial performance and efficiency. The type of this research is descriptive research, which is research which describe a problem that exist at the present time based on the way of collecting data, arrange it, explain it, analyze and draw conclusion. The study was prepared based on the financial statements of 12 Rural Banks of Bahteramas Southeast Sulawesi and has published financial statements in the period 2014 to 2016 that have been audited. The process of collecting research data conducted on the Financial Services Authority (OJK) from September until November 2017 until the necessary data has been obtained and complete. The results of the research show that from BPR Bahteramas ratios analysis, there are some Bahcam Rural Bureau of Southeast Sulawesi which still shows inefficiency condition but some BPR have good financial efficiency and performance condition, market ratio ratio analysis using HHI and CR4 is known that some BPR still dominate market share of BPR Bahtermas customers in Southeast Sulawesi. In this case still shows the oligopoly market, while for the existing bank organizational structure is still in the category of big. In a sense, the ranks of organizations within the bank is wide enough, so that in terms of operational financing also swell.